2020
DOI: 10.1186/s12977-020-0512-z
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of describing the epidemiology of HTLV in the Amazon region of Brazil

Abstract: HTLV-1 was the first described human retrovirus and was soon found to be associated with severe clinical diseases, including a devastating lymphoma/leukemia and other inflammatory diseases. Although HTLV-2 is not usually pathogenic, it is widely distributed among native Indian populations in Brazil, particularly in the Amazon region of the country. Presently, HTLV spreads mainly by the sexual route and from mother to child, and virus persistence is an active biological factor aiding its transmission. Recently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
3
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 115 publications
(163 reference statements)
0
33
3
8
Order By: Relevance
“…It is possible that such a figure is a consequence of the higher level of risky behavior, such as injecting drug use and multiple sexual partners. Co-infections with the two viruses were not observed, unlike previous investigations with HIV-1-infected persons in the states of Para and Amapa, in which HTLV-1 and HTLV-2 co-infections were detected ( Vallinoto et al, 1998 ; Laurentino et al, 2005 ; Ishak et al, 2020 ). This indicates a low prevalence of co-infections among FSWs in the North region of Brazil.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…It is possible that such a figure is a consequence of the higher level of risky behavior, such as injecting drug use and multiple sexual partners. Co-infections with the two viruses were not observed, unlike previous investigations with HIV-1-infected persons in the states of Para and Amapa, in which HTLV-1 and HTLV-2 co-infections were detected ( Vallinoto et al, 1998 ; Laurentino et al, 2005 ; Ishak et al, 2020 ). This indicates a low prevalence of co-infections among FSWs in the North region of Brazil.…”
Section: Discussioncontrasting
confidence: 97%
“…The investigation of HTLV-1/2 infections among FSWs is the first approach in Amazon Region of Brazil, particularly in a highly endemic area of HTLV infection ( Ishak et al, 2020 ). The present study observed a higher general seroprevalence of HTLV-1 than those reported in the population of men who have sex with men (0.7%) ( Malta et al, 2010 ); candidates for blood donation in the Northeast of Brazil (1.2%) ( Ribeiro et al, 2018 ), the Brazilian state of Amazonas (0.13%) ( Morais et al, 2017 ) and in non-FSW women who had a similar socioeconomic profile, such as pregnant teenagers (0.6%) ( Guerra et al, 2018 ) and women from Belém, Pará (1.4%) ( Silva et al, 2018 ) and parturients (0.4%) of Salvador, Bahia ( Vargas et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HTLV-1 is mainly prevalent in the Caribbean, South and Central America, Central and Western Africa, Southwestern Japan, Australia and Melanesia[ 4 ]. HTLV-2 has a more restricted distribution than HTLV-1, and is predominately prevalence among some Native Americans and Central African tribes.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the epidemiology of HTLV-1 and HTLV-2 is a key factor in explaining the origin of the viruses worldwide, particularly in South America and Brazil. Unfortunately, epidemiological information is sometimes old, with conflicting results, and consequently, it is not useful for defining appropriate measures for prevention and control and thus needs to be improved ( Ishak, Guimarães Ishak, and Vallinoto 2020 ). This information is useful for detecting the occurrence and frequency of the viruses in order to determine the pathways through which the virus moves and the possible routes for future spread.…”
Section: Introductionmentioning
confidence: 99%